2007
DOI: 10.1200/jco.2007.25.18_suppl.7539
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine/platinum alone or in combination with cetuximab as first-line treatment for advanced non-small cell lung cancer (NSCLC)

Abstract: 7539 Background: This randomized phase II study was conducted to evaluate the benefit of adding cetuximab, an IgG1 monoclonal antibody targeting the EGF receptor, to gemcitabine/platinum chemotherapy in patients with recurrent or metastatic NSCLC. Methods: Patients with previously untreated stage IIIB (malignant pleural effusion) or stage IV NSCLC irrespective of their EGF receptor status were eligible for this study. Patients on arm A received cetuximab (400 mg/m2 IV on day 1 followed by 250 mg/m2 weekly) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A randomized phase 2 study of cisplatin and vinorelbine with or without cetuximab demonstrated higher response rates and overall survival in favor of cetuximab‐based therapy 18. Another randomized study that compared treatment with platinum/gemcitabine with or without cetuximab also demonstrated a higher response rate and progression‐free survival with the addition of cetuximab 23…”
Section: Discussionmentioning
confidence: 99%
“…A randomized phase 2 study of cisplatin and vinorelbine with or without cetuximab demonstrated higher response rates and overall survival in favor of cetuximab‐based therapy 18. Another randomized study that compared treatment with platinum/gemcitabine with or without cetuximab also demonstrated a higher response rate and progression‐free survival with the addition of cetuximab 23…”
Section: Discussionmentioning
confidence: 99%
“…A randomized phase II trial of gemcitabine/platinum with or without cetuximab as first-line treatment for advanced NSCLC was recently reported. 20 Trends suggesting benefit were observed with higher response rates (28% versus 18%), PFS (5.1 month versus 4.2 months), and OS (12.0 months versus 9.3 months) in the cetuximab arm. A randomized multicenter phase III study of first-line taxane/carboplatin with or without cetuximab enrolled 676 advanced NSCLC patients at 97 U.S. centers.…”
Section: Overview Of Egfr Agents In Advanced Nsclcmentioning
confidence: 89%
“…In this regard, adding cetuximab to cisplatin/vinorelbine enhanced response rates (35% vs 28%) and prolonged PFS (5.0 vs 4.6 months) compared with chemotherapy alone in a randomized phase 2 study of 86 patients with previously untreated advanced NSCLC 29. Comparable results were obtained in another randomized phase 2 study when cetuximab was added to gemcitabine/platinum 30…”
Section: Challenges In Clinical Development Of Drugs For Nsclcmentioning
confidence: 92%